2016
DOI: 10.5897/ijbc2016.1025
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and temporal dynamics of foraging habitat availability for reddish egrets in the Laguna Madre, Texas

Abstract: The reddish egret (Egretta rufescens) is the rarest heron in North America and much remains to be learned about in the ecology of the species. The reddish egret is a foraging habitat specialist and relies on shallow coastal ecosystems. There is a paucity of information on foraging habitat requirements and the availability of foraging habitat throughout the annual cycle. Characteristics of foraging habitat at locations within the Laguna Madre, Texas where reddish egrets were observed foraging were measured. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 16 publications
1
12
0
Order By: Relevance
“…Reddish Egrets selected foraging habitats during the breeding period with little to no seagrass coverage. This is a characteristic of foraging habitat that has been reported during other portions of their annual cycle as well (Bates et al 2016, Koczur 2017. A recent study on the foraging dynamics of Reddish Egrets in the Laguna Madre found that, on average, egrets foraged in areas with < 12% seagrass coverage throughout the annual cycle (Bates et al 2016).…”
Section: Discussionmentioning
confidence: 58%
See 3 more Smart Citations
“…Reddish Egrets selected foraging habitats during the breeding period with little to no seagrass coverage. This is a characteristic of foraging habitat that has been reported during other portions of their annual cycle as well (Bates et al 2016, Koczur 2017. A recent study on the foraging dynamics of Reddish Egrets in the Laguna Madre found that, on average, egrets foraged in areas with < 12% seagrass coverage throughout the annual cycle (Bates et al 2016).…”
Section: Discussionmentioning
confidence: 58%
“…Last, we examined the relationships between the amount of available foraging habitat and the density of competitors around each colony on breeding pair abundance of Reddish Egrets for 22 colonies in the Laguna Madre. Available foraging habitat was previously modeled for the Laguna Madre based on bathymetry, tide gauge readings, and benthic habitat (Bates et al 2016) for the years 2010-2013. We created buffers around each colony at a 15km radius and used the spatial models of Bates et al (2016) to calculate the area of foraging habitat within each buffer.…”
Section: Foraging Habitatmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent research on this cohort of reddish egrets marked with satellite transmitters found that they exhibited a partial migration strategy, with 40% of the marked individuals migrating out of the Laguna Madre during winter months (Koczur 2017). A previous study on the spatial and temporal availability of reddish egret foraging habitat found available habitat to decrease during winter months because of changes in water level during that time (Bates et al 2016). Reddish egrets require shallow water (< 20 cm) for foraging, and winter weather conditions that lead to fluctuations in water levels reduce the amount of available shallow water habitat.…”
Section: Discussionmentioning
confidence: 98%